Indicators of stress and quality meat in broilers slaughtered by the "Halal" - Bridi, Ana Maria; Fonseca, Nilva Aparecida Nicolao; Silva, Caio Abércio da; Balarin, Mara Regina Stipp; Flaiban, Karina Keller Marques da Costa; Costantino, Camila; Tarsitano, Marina Avena; Cardoso, Thales de Almeida Bitencourt (Semina: Ciências Agrárias, 2012)
This research was aimed to evaluate the stress as well as carcass and meat quality of broilers slaughtered by the "Halal" method. 120 carcasses were evaluated, 60 broilers were slaughtered by the traditional method and 60 broilers by the "Halal" method, with live weight of 3.8 kg and 49 days old. Exsanguination blood samples were collected to measure the levels of creatine phosphokinase, lactic acid and hemogram. After the slaughter each carcass had been evaluated to verify the presence of bruises, contusions, muscle bleeding, and fractures. Initial and final pH, color (CIELAB), drip (PAG) and pressing water loss (PAP) and tenderness (shear force - FC) were measured in "Pectoralis major" muscle. The lactic acid levels were higher and lower in monocytes for the broilers slaughtered using the "Halal" method, indicating higher stress levels, while the percentage of hematocrit was great to the traditional slaughter. Animals slaughtered by the "Halal" method had wing bruises with bigger size and meat with lower pH values the initial and final, higher lightness (L*) and higher redness (a*). It was observed higher frequency of PSE carcass (pale, soft, exsudative) slaughtered by method "Halal". It is concluded that the "Halal" method of slaughter for chickens, stress increases and the size of the lesions of carcasses and higher frequency of PSE carcasses, reducing the quality of chicken meat.